PENGARUH UKURAN PERUSAHAAN, STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023 - Ilham Mustain; Batara Daniel Bagana (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The purpose of this study is to test and analyze the influence of company size, capital structure and profitability on the value of manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The data used in this study is secondary data obtained from the company's financial statements on the Indonesia Stock Exchange for the 2019-2023 period and a sample of 150 companies was obtained. The data analysis technique used is multiple linear regression analysis. The sampling method in this study uses the purposive sampling method. The size of the company is proxied by SIZE, the capital structure is proxied by the Debt to Equity Ratio (DER), the profitability is proxied by Return On Asset (ROA) and the value of the company is proxied by Price to Book Value (PBV). Profitability partially has a significant effect on the company's value. Meanwhile, the size of the company and the capital structure have no effect on the value of the company.